Towards alterity in interaction codesign - Matos, Ecivaldo De Souza; Zabot, Diego; Garrido, Filipe Adeodato; Dos Santos, Juliana Maria Oliveira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
Codesign is an approach that seeks the active participation of all stakeholders, including end users, valuing their contributions and considering their needs and experiences. However, a common challenge in codesign is the issue of alterity, which involves awareness and consideration of differences among people. Alterity is crucial to ensure the inclusion and relevance of design solutions for all involved parties. One of the problems related to alterity in codesign is the marginalization or lack of adequate representation of certain voices. This can lead to solutions that do not meet the needs of all users. It is essential to address this issue by including different perspectives, active listening, and consideration of the needs of diverse groups, aiming for alterity and accessibility throughout the design process. This paper presents examples of how alterity can or cannot manifest in interaction codesign processes, even when equitable participation is prompted and encouraged. As a methodology, we will use the Semio-Participatory Interaction Design Process (SPIDe) as a codesign process in two different implementations.